2012
DOI: 10.1016/j.aorn.2011.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an Intraoperative Clinical Experience for Senior Level Baccalaureate Nursing Students

Abstract: Perioperative nursing is a specialty that has been eliminated from many nursing education programs. With the loss of perioperative clinical experiences, the number of students pursuing a career in perioperative nursing after graduation has declined. A faculty member at one Midwestern school of nursing developed and implemented a perioperative clinical experience for senior-level baccalaureate nursing students in a critical care nursing course. This program, developed with the assistance of four local hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…As a result, students do not become interested in the specialty and may seek employment elsewhere. The future of perioperative nursing may depend on nursing students having more well‐rounded educational experiences . A 2007 study of 247 perioperative nurses representing the Baby Boomers (born between 1943 and 1960) and Generation Xers (born between 1961 and 1977) found that nurses who had any type of perioperative exposure during their nursing education had been influenced to consider a perioperative nursing career …”
Section: Perioperative Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, students do not become interested in the specialty and may seek employment elsewhere. The future of perioperative nursing may depend on nursing students having more well‐rounded educational experiences . A 2007 study of 247 perioperative nurses representing the Baby Boomers (born between 1943 and 1960) and Generation Xers (born between 1961 and 1977) found that nurses who had any type of perioperative exposure during their nursing education had been influenced to consider a perioperative nursing career …”
Section: Perioperative Educationmentioning
confidence: 99%
“…Some nursing program administrators and faculty members have integrated a perioperative clinical experience into the existing required clinical courses . Nursing students are able to choose to spend their clinical experiences for a required clinical course in the OR rather than on a medical‐surgical or critical‐care unit.…”
Section: Perioperative Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other schools have implemented perioperative clinical rotations during students' senior year with success. 7 We have found early introduction to the perioperative experience has provided valuable skills that support optimal patient care and has piqued the interest of multiple students in working in the perioperative specialty after graduation. In the literature, this finding is aligned with the goal of enhanced attraction to and postgraduate recruitment in perioperative nursing.…”
Section: Academic-practice Partnership: Costs and Benefitsmentioning
confidence: 99%
“…The global move from hospital to university education brought changes to undergraduate nursing education, one of which was the gradual phasing out of perioperative nursing from the curricula of most nursing schools 9 ; currently, a structured clinical rotation in this specialty area of nursing is rarely offered to undergraduates 4 . Undergraduate perioperative experiences in Australia 5 are similar to those in the United States, 4 the United Kingdom, 10 Canada, 11 and New Zealand 12 and range from a reintroduction of perioperative nursing to the core curricula of some universities and may include offering perioperative nursing as an elective subject or offering student observational visits to the OR.…”
Section: Literature Reviewmentioning
confidence: 99%